112k views
1 vote
1. (4a - 5) + (3a + 6)

User Daionne
by
5.1k points

2 Answers

5 votes

Answer:

a = -2 OR 5/4

Explanation:

(4a - 5) + ( 3a + 6)

Expanding the brackets

12a^2 + 24a - 15a - 30

Factorizing ...

12( a + 2) - 15 ( a + 2)

(a + 2) ( 12a - 15) = 0

Therefore:

(a + 2) = 0

OR

(12a - 15) = 0

Simplifying further:

From a + 2 = 0

a = -2

OR

12a -15 = 0

12a = 15

a = 15/12

a = 5/4

a = -2 or 5/4

User Hyperdrive
by
5.1k points
5 votes

Good evening ,

Answer:

(4a - 5) + (3a + 6) = 7a + 1

Explanation:

(4a - 5) + (3a + 6) = (4a + 3a) + (6-5) = 7a + 1.

:)

User Kemal Kaplan
by
4.4k points